TRAUMA NARRATION AND FRAGMENTED MEMORY IN POSTCOLONIAL WOMEN’S FICTION - Sofia Romano (International Journal of Literature and Language Studies, 2026)
This article analyzes fragmented memory as a narrative strategy in postcolonial women’s fiction. The study responds to the problem that postcolonial trauma is sometimes read mainly through historical content, while the broken form of narration itself carries ethical and political meaning. Using comparative close reading informed by trauma theory and postcolonial criticism, the article analyzes selected novels by women writers from South Asia, Africa, and the Caribbean. The findings indicate that fragmentation, repetition, silence, and temporal disruption represent not only psychological injury but also resistance to colonial and patriarchal demands for orderly testimony. The article argues that narrative discontinuity should be interpreted as an active literary method that protects difficult memory while making social violence legible. By connecting language, literary form, and interpretation, the study offers a concise contribution to current debates in literature and language studies.